2016
DOI: 10.1371/journal.pone.0168346
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Podocyte Loss Is Increased in Patients with Fabry Disease and Correlates with Clinical Severity of Fabry Nephropathy

Abstract: Chronic kidney disease is a major complication of Fabry disease. Podocytes accumulate globotriaosylceramide inclusions more than other kidney cell types in Fabry patients. Podocyte injury occurs early in age, and is progressive. Since injured podocytes detach into the urine (podocyturia), we hypothesized that podocyturia would increase in Fabry patients and correlate with clinical severity of Fabry nephropathy. Urine specimens from 39 Fabry patients and 24 healthy subjects were evaluated for podocyturia. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 44 publications
4
37
0
1
Order By: Relevance
“…It has been previously shown that the renal disease course in N215S FD subtype of both male and female follows a rather slow progression compared to males with classical FD (Thomas et al 2015). Progression of renal involvement in FD is multifactorial but the reasons for a more indolent course in N215S FD subtype remain poorly understood (Najafian et al 2011;Fall et al 2016). Furthermore, there was evidence of subclinical brain involvement in the form of white matter changes on brain MRI.…”
Section: Discussionmentioning
confidence: 87%
“…It has been previously shown that the renal disease course in N215S FD subtype of both male and female follows a rather slow progression compared to males with classical FD (Thomas et al 2015). Progression of renal involvement in FD is multifactorial but the reasons for a more indolent course in N215S FD subtype remain poorly understood (Najafian et al 2011;Fall et al 2016). Furthermore, there was evidence of subclinical brain involvement in the form of white matter changes on brain MRI.…”
Section: Discussionmentioning
confidence: 87%
“…Patients are found to have glomerular disease and proteinuria resulting from GSL-laden podocytes that eventually detach (32). Proximal and distal tubule abnormalities also develop (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Progressive damage of the glomerular filtration barrier plays an important role in the development of albuminuria/proteinuria and focal and segmental glomerular sclerosis in general, leading to progressive organ failure in kidney diseases, including Fabry disease [1,2,6]. In particular, the role of podocyte damage has been highlighted in Fabry nephropathy, and early structural and functional damage as well as podocyturia have been linked to podocyte Gb3 deposits and clinical disease in Fabry disease [7,8]. For assessment of disease severity and renal effect of enzyme replacement therapy, histopathologic examination of glomerular, tubulointerstitial and vascular kidney biopsy compartments is pivotal.…”
Section: Introductionmentioning
confidence: 99%